2017
DOI: 10.1016/j.ccell.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Direct Activation of BAX by BTSA1 Overcomes Apoptosis Resistance in Acute Myeloid Leukemia

Abstract: SUMMARY The BCL-2 family protein BAX is a central mediator of apoptosis. Overexpression of anti-apoptotic BCL-2 proteins contributes to tumor development and resistance to therapy by suppressing BAX and its activators. We report the discovery of BTSA1, a pharmacologically optimized BAX activator that binds with high affinity and specificity to the N-terminal activation site and induces conformational changes to BAX leading to BAX-mediated apoptosis. BTSA1-induced BAX activation effectively promotes apoptosis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
163
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(168 citation statements)
references
References 55 publications
5
163
0
Order By: Relevance
“…Our results showed that cytosolic cytochrome c levels increased while the mitochondrial cytochrome c levels decreased in BZML‐treated A549 and A549/Taxol cells. Additionally, mitochondrial outer membrane permeabilization can be affected by the Bcl‐2 family proteins . We found that BZML could time dependently up‐regulate the expression of Bax and down‐regulate the expression of Bcl‐2 in A549 and A549/Taxol cells (Figure C).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Our results showed that cytosolic cytochrome c levels increased while the mitochondrial cytochrome c levels decreased in BZML‐treated A549 and A549/Taxol cells. Additionally, mitochondrial outer membrane permeabilization can be affected by the Bcl‐2 family proteins . We found that BZML could time dependently up‐regulate the expression of Bax and down‐regulate the expression of Bcl‐2 in A549 and A549/Taxol cells (Figure C).…”
Section: Resultsmentioning
confidence: 85%
“…12 Our results showed that cytosolic cytochrome c levels increased while the mi- permeabilization can be affected by the Bcl-2 family proteins. 34,35 We found that BZML could time dependently up-regulate the expression of Bax and down-regulate the expression of Bcl-2 in A549 and A549/Taxol cells ( Figure 3C). Importantly, caspase-9…”
Section: The Mitochondrial Apoptotic Pathway Is Only Activated In Bmentioning
confidence: 91%
“…One of these drugs, Venetoclax, is specific for heterodimers containing Bcl-2 and has been approved by the FDA to treat a certain form of chronic lymphocytic leukemia (Cang et al, 2015). In addition, compounds directly activating Bax can also promote MOMP and apoptosis (Reyna et al, 2017). MOMP has therefore been validated as a key process promoting cell death.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the liposome permeabilization assay has been adapted as a screening tool to identify and characterize peptides, small molecules or antibodies that specifically bind to BCL-2 family members and modulate their function [79]. For instance, a small molecule that directly induces the activation of the BAX trigger site was characterized using this permeabilization assay [10]. Additionally, the inhibitory potential of MCL-1 small molecules binders was determined with this biochemical technique [11].…”
Section: Introductionmentioning
confidence: 99%
“…To quantify membrane permeabilization, a polyanionic dye (ANTS: 8-aminonaphthalene-1,3,6-trisulfonic acid) and a cationic quencher (DPX: p -xylene-bis-pyridinium bromide) are incorporated within the liposomes [6]. As the liposome is permeabilized by activated BAX [10] or BAK [15], ANTS and DPX diffuse apart, and an increase in fluorescence is detected using a fluorescence plate reader. Here we will discuss in more detail the experimental procedures to measure tBID-induced BAX-mediated permeabilization of liposomes.…”
Section: Introductionmentioning
confidence: 99%